Analisis Tingkat Kepuasan Penghuni Rumah Tinggal Berkonsep Green Home Di Kota Padang - Arman, Utami Dewi; Imani, Rafki; Ilfa, Ida (Jurnal Bangunan, Konstruksi & Desain, 2025)
A green home is defined as a residential concept designed with attention to the principles of sustainability in design, starting from energy efficiency, water management, selection of environmentally friendly materials, to the creation of good indoor environmental quality. The development of green housing in Padang city has begun to increase over time, but the success of a green home housing is indicated by the level of satisfaction of its residents. This study aims to identify and analyze the level of satisfaction of residents of residential houses with a green home concept. Data were collected based on a questionnaire survey and used the Customer Satisfaction Index (CSI) method to analyze the level of satisfaction of residents. Natural lighting, air circulation in the house and comfortable room temperature, design with efficient use of energy and water, the availability of green open space, noise control, waste management, and the use of quality and environmentally friendly materials are the main factors that influence the level of satisfaction and are important for residents of residential houses with a green home concept. The results of the CSI calculation of the three green home concept housing surveyed were 76.69% which is interpreted as a "satisfaction" level although there are still shortcomings in certain aspects that are used as evaluation material for improving the quality of green home housing and the expectations of residents in the future.